Gastric cancer with distinct Epstein-Barr virus-positive and -negative tumor components and their whole exome sequencing result: a case Report - Ki Bum Park; An Na Seo; Moonsik Kim (BMC, 2023)
Abstract Background Epstein-Barr virus (EBV)-associated gastric cancer exhibits distinct clinicopathologic characteristics, showing a good response to immune checkpoint inhibitors and a favorable prognosis. However, gastric cancer comprising distinct EBV-positive and -negative components in a single mass have been rarely reported, and their detailed genetic characteristics have not yet been investigated. Therefore, we reported the case of gastric cancer exhibiting distinct EBV-positive and -negative areas and further investigated its genetic characteristics. Case presentations A 70-year-old man underwent distal gastrectomy for gastric cancer, which was detected during a routine health check-up. EBV-encoded RNA in situ hybridization revealed distinct EBV-positive and -negative components at each other's borders, morphologically consistent with collision tumor. We separately sequenced EBV-positive and -negative tumor areas through whole exome sequencing (WES) with matched normal tissue. Remarkably, both EBV-positive and -negative areas shared pathogenic mutations of ARID1A, KCNJ2, and RRAS2. Furthermore, they shared 92 somatic single nucleotide variants and small insertion or deletion mutations, of which 32.7% and 24.5% are EBV-positive and -negative tumor components, respectively. Conclusions WES results suggested that gastric cancer with distinct EBV-positive and -negative tumor components, formerly categorized as a collision tumor, can be clonally related. EBV-negative tumor component might be associated with loss of EBV during tumor progression.